The stratigraphy and fauna of the Hackberry stage of the Upper Devonian / by Carroll Lane Fenton and Mildred Adams Fenton. - Fenton, Carroll Lane, 1900-1969. (Tufts University. Tisch Library., 2019)
1 online resource (xi, 260 pages) : frontispiece (map) illustrations, xlv plates, double table, diagrams.